Risk factors for gastric neuroendocrine tumors - Débora Martins Moreira de Souza Leão (2021)
Background: Gastric neuroendocrine tumors (NETs) are a rare type of neoplasm defined as well-differentiated gastric neuroendocrine neoplasms (NENs), which are epithelial neoplasms with neuroendocrine differentiation located in the stomach mucosa. This theme has become increasingly important, as its incidence has increased in recent years and little is known about its etiology. Aim: Evaluate risk factors present in the different types of gastric neuroendocrine tumors based on data from a Portuguese tertiary hospital. Methods: We retrospectively collected data from 67 patients with suspected gastric neuroendocrine pathology diagnosed between 2008 and 2020 in a tertiary hospital (Hospital São João, Porto, Portugal). We compared the 3 types of gastric NET for possible risk factors found in our database and described in the literature. For this comparison, we applied one-way ANOVA test and Pearson's Chi-square test with Fisher's exact test for continuous and categorical variables, respectively. It was considered significant when p <0.05. Results: Significant differences between groups were observed for the factors age at diagnosis, atrophic gastritis and gastric polyps. For the first, there was a higher mean age of type III in our sample compared to type I, and in the other two, the most significant difference was for the absence of atrophic gastritis and gastric polyps in type III NETs. Conclusion: We consider that regarding gastric neuroendocrine tumors we still have a lot to understand, and the etiopathogenesis still needs to be clarified.